Knowledge and Practice Regarding Topical Corticosteroids Among Dispensers in Community Pharmacies of Kathmandu Valley: A Cross-Sectional Survey - Shrestha, Shristi; Joshi, Smita; Tamang, Ram K (Journal of Institute of Medicine Nepal, 2021)
Introduction Topical corticosteroids (TCS) abuse and misuse are constantly rising in an alarming proportion, the main reason for this being free availability of such drugs over the counter (OTC) and pharmacists are one of the major prescribers of TCS. The present study was thus conducted to address the gap in information regarding the knowledge and practice of using corticosteroids among dispensers in community pharmacies. Methods A descriptive cross-sectional survey was carried out among the dispensers in community pharmacies inside Kathmandu valley from 1st March 2020 to 31st March 2021. A survey was conducted with a questionnaire which included questions to assess the knowledge and practice regarding TCS among dispensers in community pharmacies. Microsoft Excel 2010 and SPSS 16 (Statistical Package for Social Science) were used for data analysis. Results Among 209 participants, 83.73% of the participants had education related to pharmacy. They had good knowledge about brand names, generic names, and side effects of steroids. Maximum number (40.19%) of the participants responded that while coming to buy steroid creams, the patients come without prescription but with the name or cover of medicine. Majority of participants (66.51%) responded that they encounter 1-5 patients per day with recurrence of skin problems on stopping the creams. Conclusion The dispensers at community pharmacies reported having good knowledge about TCS. However, there is a need to strengthen the knowledge regarding indications of TCs including ethical and rational use of TCs among the dispensers in community pharmacies.